Clinical Results of an indivisualised mini-metal implant for Cartilage lesions in the knee. Issue 6 (28th June 2019) - Holz, Johannes; Spalding, Tim; Karl, Eriksson; Jung, Tobias M.; Verdonk, Peter; Kösters, Clemens
Aims and Objectives: We report prospective detailed results of patients undergoing treatment for chondral defects usingEpisealer, a patient-specific 2nd generation individualized mini-metal implant, based on a three dimensional MRI planing. Materials and Methods: Analysis of consecutive patients from 13 surgeons. Total of 98 patients, of which 59 patients (25 men, 34 women) with focal cartilage lesions ICRS grade 3 or 4 underwent partial resurfacing, 48 on medial condyle, 4 lateral condyle and 7 on trochlea. Mean age 48 (27-67) years, mean BMI 28 (21-41). 64% had failed previous cartilage surgery. Detailed specific MRI data was used to manufacture patient-specific implants and guide instruments, to fit the unique anatomy of each individual knee. Implants were uncemented and made of cobalt-chrome, double coated with hydroxyapatite on top of titanium. Demographic, operative and clinical scores (VAS and KOOS) were collected preop and at 6 months, 1 and 2 years postoperatively. Results: All mean KOOS domain scores were significantly improved at 1 and 2 years (p<0.05). Mean preoperative aggregated KOOS (37) improved to 62 at 12 months and remained at 62 also at 24 months (n=32), (p<0.05). Mean VAS score improved from 65 preoperatively to 37 at 24 months. All mean KOOS domain scores were significantly improved at 1 and 2 years (p<0.05). 2 patients (3.4%) underwent revision (at 9 months for infection and at 30 months for progression of arthritis). Conclusion: The study shows excellent early clinical results in the treatment of focal symptomatic cartilage lesions on the femoral condyles or trochlea with a second-generation patient specific metal implant and instruments. Adherence to strict indications has allowed for high patient reported scores and low early revision rate.